Research on noise prediction and management measures of 500kV substation based on SoundPlan - Hao Pei; Dayong Wang; Kaiyuan Shi; Yuping Wang; Ruofei Duan; Jiakai Chen; Haiyang Yu (PLoS ONE, 2026)
The noise prediction based on SoundPlan numerical simulation software is carried out for the noise of the CBD substation of the State Grid, and a comprehensive management program is designed with the prediction results. The simulation results show that for the noisy transformer, the noise can be reduced by 6–15 dB(A) through the reasonable setting of the building layout and the use of sound barriers, and the sound attenuators can be reduced by around 10 dB(A), furthermore, improving the enclosure walls can get a significant noise reduction up to 30 dB(A). And the safe emission of noise can be realized finally. The results of this simulation can provide reference for relevant engineering designers, that is, the noise of high-voltage substations in noise-sensitive areas can be simulated in advance, and comprehensive measures can be adopted to achieve noise control.